SPECTROPHOTOMETRIC DETERMINATION OF BINARY MIXTURE OF SOME - Al-Saidi, Khaleda H; Nassory, Nabil S; Maki, Shahbaz A (Al-Nahrain Journal of Science, 2018)
Derivative spectrophotometric techniques (first, second, third and fourth derivative) were developed for the determination of four â-lactam antibiotic binary mixtures; in combinations containing these compounds. The simultaneous determination of these compounds was accomplished by derivative (1D, 2D, 3D and 4D) spectrophotometric technique and applying zerocrossing technique amoxiclline trihydrate with cephalexin monohydrate (mix I) using 1D spectrum zero crossing at valley 238.2 nm, and 2D spectrum at valley 263.8 nm, respectively, amoxicllinetrihydrate with cloxacillin sodium (mix II) using 2D at valley 281 and 4D at valley 230.6, respectively, cephalexin monhydrate with cloxacillin sodium (mix III) using 1D spectrum zero crossing at 272 nm and 2D spectrum at 253.2 nm, respectively and ampicillin trihydrate with cloxacillin sodium (mix IV) using 1D at 282nm and 2D at 271.6 nm, respectively. From this studying it was noticed that in all the applications of the previous methods the correlation coefficient of calibration curves not less than 0.999 and the relative standard deviation not exceed to0.214. The four described procedures were successfully applied to the determination of these compounds in synthetic mixtures and in preparations with high percentage of recovery, accuracy and precision .The procedures do not require any separation step.